Dame Maud McCarthy: Australia's most distinguished nursing expert? - Shields, Linda; Shields, R. (The St John Ambulance Historical Society of Australia, 2010)
Dame Maud McCarthy was born in Sydney and became one of the most influential and importnat nurses of the early 20th century, yet she is largely unknown in Australia. Made a Lady (Dame) of Grace of St John in 1919, and Dame Grand Cross of the Order of the British Empire in 1918, she is important enough to have her portrait hung in the National Portrait Gallery in London. In this paper we describe Dame Maud's early life and her work during the First World War. Further work on her life will follow, as we discover more about this rather historically elusive woman whose contribution to the profession of nursing, in Australia and the UK, has been profound.